Technical competencies of oil and gas construction project managers in Malaysia - Razi, P. Z.; Saad, M. Syamsyul H.; Jamaludin, Omar (Penerbit UMP, 2021)
The oil and gas business is one of the most important and largest industries in the world. Despite the industry's large economic contribution, the output of major projects has not met expectations, particularly with regard to cost and schedule goals. project managers should possess sufficient technical knowledge and skill to perform their jobs, especially in the oil and gas industry. This paper aims to assess the level of technical competencies for oil and gas construction project managers in Malaysia.Data were collected from 75 respondents from different organisations that are involved with oil and gas construction projects in Malaysia by using a questionnaire. The current level of construction project managers in the oil and gas construction in Malaysia are mostly competent and have the most satisfied rating in determining appropriate construction methods, followed by project scheduling, directing and monitoring the project's progress. Hopefully, this study can help the industry sector, especially in oil and gas, to find competent technical PMs to ensure the project can be delivered well.